Safe and optimistic: Experiences of military members after the first repatriation of South Africans during the Covid-19 pandemic - Arendse, Danille (Scientia Militaria - South African Journal of Military Studies, 2022)
The Covid-19 pandemic presented a period of unprecedented uncertainty. The repatriation of South African citizens from Wuhan was a first for the South African government. These special circumstances of risk presented a unique opportunity to explore experiences of military members who were at the frontline. The primary aim of this study was to investigate the experiences of South African National Defence Force (SANDF) members involved in the first South African repatriation of its citizens due to the Covid-19 crisis. This included aspects such as possible stigma, perceptions and emotions towards Covid-19, repatriation, and quarantine experienced by the SANDF members. A quantitative research approach was adopted for this study. The exploratory study used purposive sampling to include only military members involved in the first South African repatriation and quarantine procedure for the Covid-19 pandemic. The research sample comprised 13 SANDF regular force members of whom 85% had tertiary qualifications. These military members were asked to complete informed consent forms and a newly created questionnaire, the Stigma and Related Matters Questionnaire. A reliability, correlation and frequency analysis was performed through SPSS. Cronbach’s alpha indicated high reliability and several strong relationships among the statements. The findings indicated that the military members involved in the return and quarantine of repatriated South Africans, were mostly positive and supportive of virus containment measures and lockdown practices. Military members did not report holding any stigmatising or discriminatory beliefs around Covid-19. These responses are in contrast with literature from other countries where people reported experiencing severe discrimination. The current responses however also support literature that reports positive perceptions on virus containment measures. More research is recommended as the Covid-19 pandemic persists in South Africa.